Appearance of fetal posterior fossa at 11–14 weeks in fetuses with Dandy–Walker malformation or chromosomal anomalies. (June 2016) - Volpe, P.; Contro, E.; Fanelli, T.; Muto, B.; Pilu, G.; Gentile, M.
ABSTRACT: Objective: To describe the sonographic appearance of fetal posterior fossa anatomy at 11–14 weeks of pregnancy and to assess the outcome of fetuses with increased intracranial translucency (IT) and/or brainstem‐to‐occipital bone (BSOB) diameter. Methods: Reference ranges for brainstem (BS), IT and cisterna magna (CM) measurements, BSOB diameter and the BS : BSOB ratio were obtained from the first‐trimester ultrasound examination of 233 fetuses with normal postnatal outcome (control group). The intraobserver and interobserver variability of measurements were investigated using 73 stored ultrasound images. In addition, a study group of 17 fetuses with increased IT and/or BSOB diameter was selected to assess outcome. Results: No significant intraobserver or interobserver variability was found for any measurement in the control group. In the study group, IT was increased in all cases and BSOB diameter was above the 95 th centile of the calculated normal range in all but two (88%) cases. In 13/17 study cases, only two of the three posterior brain spaces were recognized on ultrasound. These 13 fetuses had a larger BSOB diameter than did the four cases that showed all three posterior brain spaces, and had severe associated anomalies including Dandy–Walker malformation (DWM) and/or chromosomal anomalies. Conclusions: Visualization of the fetal posterior fossa anatomy at 11–14 weeks' gestation is feasible. Increased fluid in the posterior brain at 11–14 weeks, particularly in the case of non‐visibility of the septation that divides the future fourth ventricle from the CM, is an important risk factor for cystic posterior fossa malformations, in particular DWM, and/or chromosomal aberrations. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.